The Effect of Static Stretch and Static Contraction on Pain and Functional Ability of Knee Pain Sufferers - Fitri, Desi Tri Syawatul; Siwi, Ken; Waritsu, Cakra; Putri, Fadma (Universitas Muhammadiyah Surakarta, 2024)
Introduction: Knee pain is caused by various things, for example, excessive daily activities, obesity, osteoarthritis, trauma to the knee, age, post-surgery, and the work of housewives who often carry out excessive daily activities by squatting for a long time while washing. dishes and washing clothes, resulting in knee pain and decreased functional ability. Methods: This research is quantitative research with an experimental design (the one-group pretest-posttest) involving 10 samples of PKK mothers. The research began in May 2023-February 2024, and the intervention was carried out for 2 weeks with an intensity of 6 meetings. There are 2 instruments used, namely the visual analogue scale (VAS) to measure pain and the Jette scale to measure functional ability. Data analysis used SPSS with the Wilcoxon test. Result: Giving a combination of Static Stretch and Static Contraction can significantly reduce pain (p<0.05) and increase the functional ability of knee pain sufferers (p<0.05). Conclusion: There is an effect of the combination of Static Stretch and Static Contraction on reducing pain and increasing the functional ability of knee pain sufferers at PKK Rt 02 Dusun Manggung Sidoarjo.